3 Privileges and Penalties in The Annotated Consolidated Laws of the State of New York, at 3567 (1909). - (:unkn) unknown (My University, 1909)
Military Law, ch. 41, art. 11, § 241: No body of men, other than the active militia and the troops of the United States except such independent military organizations as were on the twenty-third day of April, eighteen hundred and eighty-three and now are, in existence, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state. No city or town shall raise or appropriate any money toward arming or equipping, uniforming or in any other way supporting, sustaining or providing drill rooms or armories for any such body of men;
Keywords: MILITIAS